Penerapan Model Atik (Amati, Tiru, Kerjakan) dalam Meningkatkan Kemampuan Motorik Kasar Anak Usia Dini Kelompok Bermain Mutiara Hati Sukoharjo - Annisa Elly; Septyana Tentiasih (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This study aims to analyze the effectiveness of the ATIK Model (Observe, Imitate, Do) in improving gross motor skills of early childhood learners at Mutiara Hati Playgroup, Sukoharjo. This research employed a quantitative approach with a pre-experimental one group pretest-posttest design without a control group. The participants consisted of 12 children aged 3–4 years selected through total sampling. Data were collected using an observation sheet measuring gross motor skills, including balance, coordination, agility, and strength. Data analysis was conducted using descriptive statistics and a paired sample t-test. The results showed that the mean pretest score was 47.8, which increased to 74.9 in the posttest, with an improvement of 27.1 points. The t-test results indicated a significance value of 0.000 < 0.05, meaning that the ATIK Model had a significant effect on improving children’s gross motor skills. These findings suggest that learning through observation, imitation, and direct practice effectively stimulates motor development in early childhood. Therefore, the ATIK Model is effective in enhancing gross motor development through active, enjoyable, and developmentally appropriate learning activities